A Missense variant in LAMA3 gene causes microcephaly and epidermolysis bullosa in a Pakistani family - Mughal, Zaib-Un-Nisa; Zai, Jawaid Ahmed; Ansar, Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: To identify the disease-causing mutation in a family with autosomal recessive primary microcephaly (MCPH). METHODOLOGY: This cross-sectional study was the continuation of an ongoing family-based study initiated in 2016 at the Department of Biochemistry, Quaid-e-Azam University, Islamabad. The family was selected randomly and recruited from Sahiwal and has three members with MCPH. DNA was isolated from blood samples and the genome-wide scan was performed to map homozygous regions. Whole exome sequencing (WES) was performed to identify the plausible gene variant. RESULTS: Whole genome data analysis identified multiple homozygous regions, but none of these contain known MCPH genes. Whole exome sequencing (WES) data identified six potentially pathogenic variants but only the Laminin subunit alpha-3 (LAMA3) (c.5260C/T) variant segregates in the family and is also present within the genomic region mapped on chromosome 18. The reevaluation of affected members of the family revealed the presence of blisters on their hands and feet indicating the presence of epidermolysis bullosa along with microcephaly. CONCLUSION: The casual finding of the LAMA3 variant (c.5260C/T; p. Arg1754Trp) and absence of any other MCPH causing variant in affected members of this family expands the phenotypic spectrum of LAMA3 associated phenotype. Therefore, we can conclude that the LAMA3 variant can probably cause recessive microcephaly and epidermolysis bullosa, but additional studies are needed to establish the role of LAMA3 in microcephaly. KEY WORDS: MCPH, LAMA3, Laminin-5, Genome scan, homozygous regions, whole-exome sequencing.